1968
DOI: 10.1172/jci105956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diphenylhydantoin on synaptosome sodium-potassium-ATPase

Abstract: A B ST R A C T Previous studies have demonstrated that electrically induced seizures in rat result in an increased brain intracellular sodium which can be decreased by treatment with sodium diphenylhydantoin (DPH). The correlation of cation transport with membrane-oriented sodiumpotassium-adenosine triphosphatase (Na-K-ATPase) prompted an investigation of the effect of DPH upon ATPase enzyme activity.Rat cerebral cortical synaptosomes isolated in Ficoll gradients were employed as the source for Na-K-ATPase. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

1970
1970
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(40 citation statements)
references
References 23 publications
(30 reference statements)
4
35
1
Order By: Relevance
“…Because enhancement of Na+K+ATPase is considered to be associated with the pharmacologic effect of DPH (22) and because, in synaptosomes, Festoff and Appel could demonstrate enhancement by DPH only at high Na:K ratios (22), we studied effects of ouabain and DPH at both the 5:1 and the 250:1 Na:K ratio. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because enhancement of Na+K+ATPase is considered to be associated with the pharmacologic effect of DPH (22) and because, in synaptosomes, Festoff and Appel could demonstrate enhancement by DPH only at high Na:K ratios (22), we studied effects of ouabain and DPH at both the 5:1 and the 250:1 Na:K ratio. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been obtained previously (Gilbert et al, 1974a, b;Gilbert & Wyllie, 1974a,b). Formby (1970) and Escueta & Appel (1970) have also reported inhibition of cerebral cortex Na+,K+-ATPase by phenytoin but Festoff & Appel (1968) found that when the ratio of sodium to potassium ions in the assay medium was above 25:1 phenytoin stimulated the enzyme. The present results do not confirm that report but it may be that it is the absolute concentrations of the ions, rather than the relative concentrations which are important.…”
Section: Discussionmentioning
confidence: 98%
“…Of the other effects of the drugs the changes which some induce in brain sodium, potassium-activated, magnesium-dependent adenosine triphosphatase (Na+,K+-ATPase, EC.3.6.1.3) activity, thereby influencing ion gradients, are of particular interest. However, whilst there is little doubt that phenytoin (diphenylhydantoin) can influence brain .Na+,K+-ATPase activity, whether inhibition or stimulation results appears to depend upon the concentrations of sodium and potassium ions in the assay medium (Festoff & Appel, 1968;Rawson & Pincus, 1968;Formby, 1970;Woodbury & Kemp, 1970;Gilbert, Buchan & Scott, 1974a;Gilbert & Wylie, 1974b;Koostra & Woodhouse, 1974). The anticonvulsant ethosuximide also inhibits Na+,K+-ATPase but previous experiments in this laboratory have failed to detect effects of phenobarbitone or acetazolamide on the activity of the enzyme ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the observations that DPH increased the rate of sodium flux in normal rat brains and decreased the intracellular brain sodium concentrations in normal rats and in rats subjected to electroshock seizures, he proposed that the anti-seizure activity results from stimulation of active sodium extrusion (1). Festoff and Appel (5) found that DPH appears to stimulate (Nat + K+)-ATPase activity in synaptosomes from rat cerebrum when the Na: K ratio is in the range 50: 1. The experiments reported here with NaI-extracted brain microsomes confirm the apparent stimulatory effect of DPH at high Na: K ratios and show that this effect results from a decrease in Na inhibition.…”
Section: Methodsmentioning
confidence: 99%
“…There is now considerable evidence that active Na' transport is linked to (Nae + K+)-activated adenosine triphosphatase (2,3). Studies on this enzyme have shown that DPH inhibits the enzyme activity in brain microsome extracts (4) and in synaptosomal preparations (5,6) under conditions of low Na: K ratios although it appears to stimulate enzyme activity in synaptosomes under high Na: K ratios (5). In addition, DPH stimulates K+ transport under certain conditions in synaptosomes (7).…”
Section: Introductionmentioning
confidence: 99%